Syndecan 4 Upregulation on Activated Langerhans Cells Counteracts Langerin Restriction to Facilitate Hepatitis C Virus Transmission - Nijmeijer, Bernadien M.; Eder, Julia; Langedijk, Catharina J. M.; Kaptein, Tanja M.; Meeussen, Sofie; Zimmermann, Pascale; Ribeiro, Carla M. S.; Geijtenbeek, Teunis B. H. (Frontiers in Immunology, 2020)
Sexually transmitted Hepatitis C virus (HCV) infections and high reinfections are a major concern amongst men who have sex with men (MSM) living with HIV-1 and HIV-negative MSM. Immune activation and/or HIV-1 coinfection enhance HCV susceptibility via sexual contact, suggesting that changes in immune cells or factors are involved in increased susceptibility. Activation of anal mucosal Langerhans cells (LCs) has been implicated in increased HCV susceptibility as activated but not immature LCs efficiently retain and transmit HCV to other cells. However, the underlying molecular mechanism of transmission remains unclear. Here we identified the Heparan Sulfate Proteoglycan Syndecan 4 as the molecular switch, controlling HCV transmission by LCs. Syndecan 4 was highly upregulated upon activation of LCs and interference with Heparan Sulfate Proteoglycans or silencing of Syndecan 4 abrogated HCV transmission. These data strongly suggest that Syndecan 4 mediates HCV transmission by activated LCs. Notably, our data also identified the C-type lectin receptor langerin as a restriction factor for HCV infection and transmission. Langerin expression abrogated HCV infection in HCV permissive cells, whereas langerin expression on the Syndecan 4 expressing cell line strongly decreased HCV transmission to a target hepatoma cell line. These data suggest that the balanced interplay between langerin restriction and Syndecan 4 transmission determines HCV dissemination. Silencing of langerin enhanced HCV transmission whereas silencing Syndecan 4 on activated LCs decreased transmission. Blocking Heparan Sulfate Proteoglycans abrogated HCV transmission by LCs ex vivo identifying Heparan Sulfate Proteoglycans and Syndecan 4 as potential targets to prevent sexual transmission of HCV. Thus, our data strongly suggest that interplay between receptors promotes or restricts transmission and further indicate that Syndecan 4 is the molecular switch controlling HCV susceptibility after sexual contact.